The Shelf-Life Prediction of Black Garlic Chili Sauce and “Cahyo” Garlic Chili Sauce with Accelerated Shelf-Life Testing (ASLT) Method Based on The Arrhenius Model - Afridho Laksono Indra Purnama; Ratna Yulistiani; Luqman Agung Wicaksono; Wahyu Setyarini; Radita Yuniar Arizandy; Nadya Dwi Putri Febrianti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Sambal is often found in various menu variants served in the Indonesian food industry; this is a supporting factor for creating bottled chili sauce. In this research, fermented black garlic chili sauce was made with black garlic as raw material to provide added value in the form of antibacterial and antioxidant compounds, as well as giving a novelty value to the product as well as a differentiator in the elements of color, aroma, consistency, and taste of the product. The final product consumers receive is compared to